Development of Digital Corporate University Strategy at the Indonesian FDA to Strengthening Human Resources in Improving Competitiveness and Public Health through Quality Food and Drug Control in Indonesia - Perdhana Ari Sudewo; John Welly (Journal of International Conference Proceedings (JICP), 2021)
The quality of food and drug is a part that determines the level of public health in Indonesia. Nevertheless, several problems must be faced that cause food and drug control to be considered ineffective in the implementation, involve the weakness of the human resources of food and drug control competencies. This study aims to develop a learning and development strategy at the Indonesian Food and Drug Authority (Indonesian FDA) to strengthen human resources for solving the problem of food and drug control in Indonesia. The study was carried out through survey, focus group discussion, interview, dan literature study to get the data analyzed and the conclusion. The result findings showed that Corporate University with college and school strategy and digital learning relevant to human resources of food and drug control condition that spread in all Indonesia, in the Indonesian FDA office or other government agencies of central and regional government. This strategy is a new approach in learning and development for strengthening human resources of food and drug control to support improved public health through quality food and drug control and support for increasing competitiveness of Indonesian food and drug industries. This study can be helpful for public officials or policymakers in human resources development, particularly in learning and development program designing.